From conflict to complementarity: Reconciling international counterterrorism law and international humanitarian law. (April 2021) - Saul, Ben
Abstract: This article clarifies the ongoing confusion in doctrine and practice about both the actual and optimal interaction between international counterterrorism law (CTL) and international humanitarian law (IHL) in armed conflict. It discusses the advantages and disadvantages of the co-application of CTL with IHL, before considering a variety of techniques for mutually accommodating the interests of both regimes, particularly through partial exclusion clauses in counterterrorism instruments or laws. It concludes by identifying the optimal approach to the relationship between CTL and IHL, which recognizes the legitimate interests of both fields of law while minimizing the adverse impacts of each on the other.